Exploring the role of academic heads in maintaining the quality of teaching and learning within their departments: a case study of a private university - Tumar, Annyza; Asimiran, Soaib; Lope Pihie, Zaidatol Akmaliah; Ismail, Ismi Arif (2016)
Higher education institutions are generally concerned with the quality of their graduates. Many institutions put in a lot effort in ensuring quality teaching and learning experience to their students because this is a reflection on the quality of the institutions themselves. This paper reports the findings of a qualitative case study at a Malaysian private university. It explores the meaning of quality teaching and learning, form the perspectives of academics and their heads of departments. It also reviews the roles of the heads of departments in maintaining the quality of teaching and learning within their departments. Data was derived from focused group interviews with academics and individual interviews with heads of departments. Findings indicate that heads of departments play a very important role in three areas: 1. assessing the quality of teaching and learning 2. identifying academic staff development needs; 3. supporting continuous professional development activities within the departments. In addition, in efforts to improve the quality of their teaching, academics were found to be more satisfied with professional development activities at department level than activities carried out at institutional level. The paper concludes with suggestions on strategies for enhancing professional development opportunities for improving teaching and learning within the departments and the institution itself.